Continuous summer export of nitrogen-rich organic matter from the Greenland Ice Sheet inferred by ultrahigh resolution mass spectrometry - Lawson, Emily C.; Bhatia, Maya P.; Jemma, Wadham L.; Elizabeth, Kujawinski, B. (ACS Publications, 2014)
Runoff from glaciers and ice sheets has been acknowledged as a potential source of bioavailable dissolved organic matter (DOM) to downstream ecosystems. This source may become increasingly significant as glacial melt rates increase in response to future climate change. Recent work has identified significant concentrations of bioavailable carbon and iron in Greenland Ice Sheet (GrIS) runoff. The flux characteristics and export of N-rich DOM are poorly understood. Here, we employed electrospray ionization (ESI) coupled to Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) to determine the elemental compositions of DOM molecules in supraglacial water and subglacial runoff from a large GrIS outlet glacier. We provide the first detailed temporal analysis of the molecular composition of DOM exported over a full melt season. We find that DOM pools in supraglacial and subglacial runoff are compositionally diverse and that N-rich material is continuously exported throughout the melt season as the snowline retreats further inland. Identification of protein-like compounds and a high proportion of N-rich DOM, accounting for 27-41% of the DOM molecules identified by ESI FT-ICR MS, may suggest a microbial provenance and high bioavailability of glacially-exported DOM to downstream microbial communities.